USE OF DEMONSTRATION METHODS IN ACHIEVEMENTS LEARNING OUTCOMES IN SEWING FASHION TRAINING - Siti Kulsum (IKIP Siliwangi Bandung, 2018)
In the National Education System Law Number 20 of 2003 Article 26 paragraph 5 states that